Penggunaan Model e-Media Berbasis Komputer dalam Pembangunan Sistem e-Learning (Studi Kasus: e-Media untuk Pembelajaran Gerak Osilasi) - Yugowati Praharsi (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2004)
The quality and potential of human resources have an important rule in thedevelopment of a country. One of the challenges is the big number of human resources whoare spread to education distribution level. So it is needed an e-Media which can be used topresent information which can guarantee to do interaction among them. This paper willpropose the using an e-Media based on computer to e-Learning development, which will beimplemented on oscillation motion learning with Maple programming in Faculty ofInformation Technology–Satya Wacana Christian University in CD form.This e-Media modelcan create flexibility in learning of method, time and interactivity aspects and also canincrease interaction between teacher and student. Furthermore, this e-Media model can bedeveloped as a tool of knowledge management application development and a tool of learningcontent management system application development.Keywords: e-media, e-learning, cd, knowledge management, learning content managementsystem.